Pharmacovigilance in Psychiatry - Spina, Edoardo; Trifirò, Gianluca (Springer International Publishing : Imprint: Adis, 2016)
The first authoritative textbook specifically addressing issues of the field, this book delivers a focused discussion on several themes in psychiatry while providing a sound background on pharmacovigilance. Internationally-recognised researchers, clinicians and pharmacovigilance experts contributed to this textbook, giving it the benefit of different perspectives and years of experience. Pharmacovigilance in psychiatry provides a thorough introduction to this field but goes on to explore advanced themes such as methodologies and resources used for pharmacovigilance in psychiatry, challenges as well as most recent developments to this field, making it suitable for under-graduates, graduate and post-doctoral students and persons working pharmacovigilance who seek to broaden their knowledge on this subject.